Vegetable oils as green solvents for carotenoid extraction from pumpkin (Cucurbita argyrosperma Huber) byproducts: Optimization of extraction parameters. Issue 7 (23rd June 2021) - Portillo‐López, Rubén; Morales‐Contreras, Blanca E.; Lozano‐Guzmán, Eduardo; Basilio‐Heredia, José; Muy‐Rangel, María D.; Ochoa‐Martínez, Luz A.; Rosas‐Flores, Walfred; Morales‐Castro, Juliana
Abstract : Abstract: Pumpkin pulp is the main waste generated by pumpkin seed growers. This agro‐industrial waste is a valuable source of bioactive compounds, especially carotenoids (β‐carotene, α‐carotene, and lutein), which exhibit a broad spectrum of health‐promoting effects. In this study, vegetable oils (canola, corn, and soybean oil) were used as green solvent alternatives to conventional organic solvents for carotenoid extraction from dried pumpkin pulp (DPP) waste. The highest carotenoid extraction yield (CEY) was obtained with canola oil, at a 1:10 DPP/oil ratio. Response surface methodology (RSM) was used to optimize the extraction process parameters (temperature, time, and stirring rate) through a Box‐Behnken design (BBD) maximizing CEY in canola oil. The extraction temperature and stirring rate were found to have a significant linear and quadratic effect, respectively, on CEY. Optimum conditions were achieved at 21.8 min, 250 rpm, and 60°C. Under these optimized conditions, the estimated value for CEY was 378.1 µg β‐carotene equivalents/g of DPP, corresponding to 61.6% of the total carotenoid content present in the DPP. In contrast, the observed experimental value was 373.2 µg β‐carotene equivalents/g of DPP (61.2%). The experimental value was very close to the estimated value, which verifies the model's adequacy and fit. This study shows an alternative method to extract carotenoids from DPP with canola oil, obtaining an oil naturally enriched with carotenoids that could be used as a potential functional ingredient in the development of food, cosmetics, and medicinal products. Practical Application: Pumpkin by‐products are a potential carotenoid source. Vegetable oil can be used as an alternative solvent for carotenoid extraction from pumpkin residues to obtain an enriched carotenoid oil that can be used to formulate food products.